Cloudburst analysis in the Nainital district, Himalayan Region, 2021 - Kishan Singh Rawat; Smruti Ranjan Sahu; Sudhir Kumar Singh; Anil Kumar Mishra (Discover Water, 2022)
Abstract Some areas of Uttarakhand faced heavy rainfall during October 17-19th, 2021. In October, rainfall hit its all-time high. A sudden heavy rainfall occurred due to this, which has affected the daily life of humans. More than 50 casualties were recorded during this study period. The main focus of this study was to monitor the Uttarakhand flood event using satellite observations. The Nainital and Almora districts of the state were mainly affected by this sudden heavy rainfall. On October 18th, Nainital received the maximum rainfall of about 21.51 mm at 11:00 am (UTC). The Nainital district has recorded a cumulative rainfall of more than 300 mm on October 18th, 2021. From the observation, we find out that this heavy rainfall occurred due to a sudden cloud burst at Ramgarh in Nainital district. This sudden extreme rainfall further caused a flash flood in the study area. The rainfall pattern has moved towards Assam after it caused a flash flood in the Nainital district of Uttarakhand, India.